2022
DOI: 10.1080/21655979.2022.2059609
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA circ_0004277 Inhibits Acute Myeloid Leukemia Progression Through MicroRNA-134-5p / Single stranded DNA binding protein 2

Abstract: Circular RNAs (circRNAs) are crucial non-coding RNAs in the process of tumorigenesis. Nevertheless, the biological function of circ_0004277 in acute myeloid leukemia (AML) is blurred. Microarray data of circRNAs were utilized to evaluate circRNAs’ differential expression in AML. Quantitative real-time polymerase chain reaction (qRT-PCR) was executed to determine circ_0004277 and microRNA-134-5p (miR-134-5p) expression levels. The growth, migration and invasion of AML cells were tested by the cell counting kit-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…A previous study showed that high expression of miR-134-5p promotes the relapse of early-stage lung adenocarcinoma, leading to poor survival 26 . Other studies have shown that miR-134-5p suppresses the aggressiveness and growth of AML cells 27 . However, the role of miR-134-5p in HCC remains elusive.…”
Section: Discussionmentioning
confidence: 93%
“…A previous study showed that high expression of miR-134-5p promotes the relapse of early-stage lung adenocarcinoma, leading to poor survival 26 . Other studies have shown that miR-134-5p suppresses the aggressiveness and growth of AML cells 27 . However, the role of miR-134-5p in HCC remains elusive.…”
Section: Discussionmentioning
confidence: 93%
“…CircPLXNB2 is a valuable predictor of prognosis in patients with AML (Lin, Wang, Bian, Sun, Guo, Kong, Zhao, Guo, Li, Wu, Wang, Wang and Li, 2021). Further, Liu et al (2022) found that expression of hsa_circ_0004277 can be restored after chemotherapy in patients with AML, suggesting that its up-regulation is associated with successful treatment; hence, hsa_circ_0004277 is a potential diagnostic marker and treatment target in AML. Further, circRNF220 can distinguish AML from ALL and other hematological malignancies, while high circRNF220 expression is an unfavorable prognostic marker of recurrence, due to its role in sequestration of miR-30a, which increases MYSM1 and IER2 expression and is implicated in AML relapse (Liu et al, 2021).…”
Section: Discussionmentioning
confidence: 98%
“…A previous study showed that high expression of miR-134-5p promotes the relapse of early-stage lung adenocarcinoma, leading to poor survival [26]. Other studies also indicated that miR-134-5p suppresses the aggressiveness and growth of AML cells [27]. However, the role of miR-134-5p in HCC remains elusive.…”
Section: Discussionmentioning
confidence: 99%